DIGITAL JUSTICE (World Bulletin of Management and Law, 2023)
The article analyzes necessity of digital justice in criminal process. In order to simplify and speed up the criminal process, proposals and recommendations for the digitalization of pretrial and judicial proceedings are scientifically substantiated
Keywords: digital justice; digital criminal case; videoconference mode